2021
DOI: 10.1038/s43588-021-00114-y
|View full text |Cite|
|
Sign up to set email alerts
|

The Inflammatory Bowel Disease Transcriptome and Metatranscriptome Meta-Analysis (IBD TaMMA) framework

Abstract: Inflammatory bowel disease (IBD) is a class of chronic disorders whose etiogenesis is still unknown. Despite the high number of IBD-related omics studies, the RNA-sequencing data produced results that are hard to compare because of the experimental variability and different data analysis approaches. We here introduce the IBD Transcriptome and Metatranscriptome Meta-Analysis (TaMMA) framework, a comprehensive survey of publicly available IBD RNA-sequencing datasets. IBD TaMMA is an open-source platform where sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(73 citation statements)
references
References 33 publications
6
67
0
Order By: Relevance
“…As a matter of fact, in both mycobiome and archaeome contexts, the use of metatranscriptomics may help to better classify and annotate the fungal and archaeal composition of the gut microbiota, as we recently reported in IBD TaMMA (Massimino et al, 2021). However, much more effort in developing and improving both sequencing and cultivation approaches is required to make plausible the mycobiome and archaeome studies to unravel their physiological properties.…”
Section: Major Challenges In Studying Mycobiome and Archeomementioning
confidence: 94%
See 3 more Smart Citations
“…As a matter of fact, in both mycobiome and archaeome contexts, the use of metatranscriptomics may help to better classify and annotate the fungal and archaeal composition of the gut microbiota, as we recently reported in IBD TaMMA (Massimino et al, 2021). However, much more effort in developing and improving both sequencing and cultivation approaches is required to make plausible the mycobiome and archaeome studies to unravel their physiological properties.…”
Section: Major Challenges In Studying Mycobiome and Archeomementioning
confidence: 94%
“…The majority of the studies reported so far elucidated the mycobiome composition in small sample-sized IBD patient cohorts, mainly on stools and exploiting targeted DNA sequencing and PCR (Mahmoudi et al, 2021). By contrast, IBD TaMMA (Massimino et al, 2021) highlighted CD and UC ilea both featuring an increased abundance of Glomerellales, Tremellales, and Hypocreales, coupled with decreased abundance of Schizosaccharomycetales. Some orders were instead differentially abundant in the two conditions.…”
Section: The Gut Mycobiomementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, despite the exponential increase in transcriptomics and metatranscriptomics studies in IBD in the past decade, such datasets are often limited by low patient numbers. Recently, a novel meta-analysis framework for transcriptome and metatranscriptome data in IBD has been introduced, called the IBD Transcriptome and Metatranscriptome Meta-Analysis (TaMMA) platform ( Massimino et al, 2021 ). The TaMMA platform collates and integrates transcriptomics (and metatranscriptomics) data from multiple IBD patient cohorts using a standardised pipeline that corrects batch effects and performs differential analysis of the data.…”
Section: Future Challenges and Potential Mitigating Strategies To Develop Network Biology Approaches For Precision Medicinementioning
confidence: 99%